A systematic review of eating disorder prevention and preventative protocols for elite female athletes in individual sports - Larsen, T. (ProQuest Dissertations Publishing, 2022)
Female athletes are at a great risk of developing an eating disorder due several risk factors. The purpose of this systematic literature review was to explore what sport psychology preventative interventions are effective for eating disorders within elite female individual-sport athletes, and to create best-practice recommendations for preventing eating disorders within this population. This project synthesized and analyzed literature related to preventing eating disorders among the elite female individual sport population, and determined which interventions were most effective and why. The results indicated sport psychology interventions such as athlete modified healthy weight focus interventions (AM-HWI) and athlete modified cognitive-behavioral-dissonance-based interventions (AM-CBT) were most effective at preventing eating disorders. Findings also suggested that interventions such as providing prevention education to coaching staff and athletes were also effective with prevention. The findings were integrated into a pamphlet that can be distributed to coaches and practitioners with the purpose of educating elite coaching staff and peers on the warning signs, risk factors, and ways to assist athletes with eating disorders.